PENGELOLAAN OBJEK WISATA PANTAI DALAM MENINGKATKAN KESEJAHTERAAN PELAKU USAHA PERSPEKTIF EKONOMI ISLAM DI DESA MATANG DANAU KECAMATAN PALOH KABUPATEN SAMBAS - Syafika, Anggi; Ananda, Iva Ashari; Gustina (Cross-Border Journal of Business Management, 2025)
The purpose of this study is to find out how the management manages coastal tourist attractions and with the management of these tourist attractions, it can improve the economy of the surrounding community, especially business actors around the beach. This study uses the theory of management and welfare, this study uses a qualitative approach that is descriptive. The results of this study indicate that the management of the Matang Danau Beach tourist attraction in Matang Danau Village, Paloh District, Sambas Regency can be said to be still not optimal because of the lack of facilities around the beach, for example there are still no prayer rooms and public toilets, but with the management of the Matang Danau beach, it can also increase the level of welfare for the surrounding community, and with the management of the beach, it can reduce coastal abrasion due to the construction of a concrete embankment to prevent seawater abrasion and also more adequate road facilities with paved roads, and the construction of the Matang Danau Beach name icon, a gazebo for visitors to take shelter. With the Management of the Matang Danau Beach tourist attraction, it has a positive impact on improving the welfare of business actors around the beach in Matang Danau Village, as evidenced by the increase in income obtained, which initially only utilized the results of farming and fishing, now there is additional income from the business being run. In terms of education and health, there has also been an increase in which the facilities are more adequate and security has been regulated by members of the tourist attraction management and there is great public awareness.